Macroeconomic Fluctuations on Financial Technology Profit: An Empirical Study on GOTO Company 2018-2024 - Baihaqqy, Mochammad Rizaldy Insan; Sobari, Sobari (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
The profitability of a company is an important aspect of the future of a company, especially companies that have gone public where financial performance is an important aspect for investors in considering investment decisions. In the context of digital era activities, various financial technologies (FinTech) have emerged which have brought about important changes in Indonesian banking. This study aims to examine the influence of macroeconomics, namely inflation and interest rates on the return on assets of GOTO Company in the period 2018-2024. The results of the study show that inflation and interest rates have no effect on the return on assets of GOTO Company. This indicates that the profitability of Fintech GOTO is not affected by inflation or interest rates, this condition indicates that there is a different pattern of influence between digital and conventional financial companies in their influence on macroeconomics and profitability.